PEMAHAMAN MASYARAKAT TENTANG PERKUATAN RUMAH DENGAN MORTAR SERAT POLYPROPYLENE - Eka Juliafad; Nevy Sandra; Jonny Mardizal; Annisa Prita Melinda (Politeknik Negeri Sriwijaya, 2022)
Pasaman District is in West Pasaman Regency, along the coast of West Sumatra at 000°05' NL – 00°03′ SL and 99°38′ – 100° 58′ EL which is adjacent to the Mentawai subduction so that this area is vulnerable to earthquakes, as happened in 2009 which caused 9108 houses to be damaged. Extensive number of damaged houses was caused by the low strength of non-engineered building. Under the threat of Mega-Earthquake from the Mentawai fault, the low capacity of community houses against earthquake forces can be a threat to the community. This Community Partnership Program (PKM) offers a solution to reduce the risk of damage to houses in Pasaman District through training in the strengthening techniques using polypropylene fiber mortar. Based on observations in the field, generally people's houses in Pasaman District have walls made of red brick. Taking into account the technical ease of implementation, affordability of costs, availability of local materials, transfer of knowledge and the application of retrofitting techniques owned by the Department of Civil Engineering, Padang State University, the reinforcement technique for brick walls with Polypropylene Fiber Mortar Plaster will be used. The training was able to increase the community's understanding of house strengthening by up to 85%, which was previously 45.4%.